Effect of Absenteeism on the Economic Performance of Small and Medium-sized Enterprises-SMEs - TRAORE , Alhousseiny Samba (International Journal of Scientific Research and Management (IJSRM), 2024)
Absenteeism has a significant impact on a company's economic performance. When employees are absent, this can lead to increased costs related to personnel management, particularly in terms of the time and money needed to find temporary replacements. In addition, absenteeism can cause a drop in productivity and quality, as well as an increase in delivery delays or production costs. The main objective of this study is to understand the consequences of absenteeism on Small and Medium Enterprises-SMEs. The study was conducted in several SMEs in Mali sharing the same challenges in terms of efficient personnel management in the face of the problem of absenteeism and with a diverse sample of professionals concerned. Through this study, we wanted to spread the effects and propose solutions for adjusting absenteeism and the weight it weighs, which preponderates on the economy of a company.